POLA HERNIA INGUINALIS LATERALIS DI RSUP PROF. DR. R. D. KANDOU MANADO PERIODE AGUSTUS 2012 – JULI 2014 - Rawis, Claudia G.; Limpeleh, Hilman P.; Wowiling, Paul A. V. (Universitas Sam Ratulangi, 2015)
Abstract: Lateral inguinal hernia is a protrusion of the abdominal wall that occurs in the inguinal region adjacent to the lateral inferior epigastric vessels. This hernia can occur due to congenital or acquired causes. Approximately 80-90% of laateral inguinal hernia was found in men and 10% in women. This study aimed to determine the pattern of lateral inguinal hernia in Prof. Dr. R. D. Kandou Manado period August 2012 - July 2014. This was a retrospective descriptive study using secondary data of lateral inguinal hernia patients in the Prof. Dr. R. D. Kandou General Hospital Manado. The results showed that there were 146 lateral inguinal hernia patients in Prof. Dr. R. D. Kandou General Hospital Manado during the period August 2012 - July 2014. The most common age group was elderly (27.4%). Male sex was the majority of the lateral inguinal hernia patients (99.3%). Patients with the layout of the lateral inguinal hernia on the right were the most cases (60.3%). The type according to the progress of the hernia was reponible (74.0%). The most frequent management of the lateral inguinal hernia patients was herniotomy with the use of mesh (73.3%).Keywords: hernia, pattern of lateral inguinal herniaAbstrak: Hernia inguinalis lateralis adalah suatu penonjolan dinding perut yang terjadi di daerah inguinal sebelah lateral pembuluh epigastrika inferior. Penyebab hernia inguinalis lateralis yaitu kongenital atau karena sebab yang didapat. Sekitar 80-90% ditemukan pada laki-laki dan 10% pada perempuan. Penelitian ini bertujuan untuk mengetahui pola hernia inguinalis lateralis di RSUP Prof. Dr. R. D. Kandou Manado periode Agustus 2012 – Juli 2014. Penelitian ini bersifat deskriptif retrospektif menggunakan data sekunder pasien hernia inguinalis lateralis di RSUP Prof. Dr. R. D. Kandou Manado. Hasil penelitian memperlihatkan 146 pasien hernia inguinalis lateralis di RSUP Prof. Dr. R. D. Kandou Manado selama periode waktu tersebut. Kelompok umur tersering ialah manula atau >65 tahun (27,4%). Jenis kelamin laki-laki merupakan mayoritas (99,3%). Pasien hernia inguinalis lateralis dengan letak di sebelah kanan merupakan kasus terbanyak (60,3%). Jenis menurut perlangsungan hernia yang tersering ialah hernia inguinalis lateralis reponibel (74,0%). Penanganan hernia inguinalis lateralis yang paling sering dilakukan ialah herniotomi disertai penggunaan mesh (73,3%).Kata kunci: hernia, pola hernia inguinalis lateralis